Siwa: A custom RISC-V based system on chip (SOC) for low power medical applications. (April 2020) - Garcia-Ramirez, Ronny; Chacon-Rodriguez, Alfonso; Molina-Robles, Roberto; Castro-Gonzalez, Reinaldo; Solera-Bolanos, Egdar; Madrigal-Boza, Gabriel; Oviedo-Hernandez, Marco; Salazar-Sibaja, Diego; Sanchez-Jimenez, Dayhana; Fonseca-Rodriguez, Melissa; Arrieta-Solorzano, Johan; Rimolo-Donadio, Renato; et al.
Abstract: This work introduces the development of Siwa, a RISC-V RV32I 32-bit based core, intended as a flexible control platform for highly integrated implantable biomedical applications, and implemented on a commercial 0.18  μ m high voltage (HV) CMOS technology. Simulations show that Siwa can outperform commercial micro-controllers commonly used in the medical industry as control units for implantable devices, with energy requirements below the 50 pJ per clock cycle.